From contractors to investors? Evolving engagement of Chinese state capital in global infrastructure development and the case of the Lekki Port in Nigeria - Hong Zhang (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2023)
Chinese companies have been seeking to climb up the value chain by becoming investors and operators of the infrastructure projects they are contracted to build. Despite their prominent market share in Africa as contractors, Chinese companies face a steep learning curve and have sought to work with other international actors from advanced economies. The industry's willingness to upgrade can harness a move away from China's lending practice that is overly reliant on sovereign loans. Host governments need to be realistic about the capabilities of Chinese companies as investors and operators, and push for localization and skill transfer.
Keywords: 330